Recommended Standards for Assessing Blood Pressure in Human Research Where Blood Pressure or Hypertension is a Major Focus - Consortium, TRUE (Journal of Hypertension and Cardiology, 2016)
Although inaccurate, non-reproducible blood pressure values can result from non-standardized assessments, recommended approaches to standardize blood pressure measurement are often not followed in research studies. An expert consensus of national and international health and scientific organizations developed recommended minimum standards for assessing blood pressure in research subjects where: 1) blood pressure or hypertension is a major endpoint, or 2) blood pressure is likely a major mediator of the research outcome. Minimum research standards are presented for training of observers, technical aspects of assessing blood pressure, and equipment for both adults and children. The standards are based on prior recommendations some of which did not conform to current evidence based methods. All new research should require adherence to these minimum standards on the patient populations described above. Readers need to use caution in interpreting studies if the standards are not met in the defined populations.
Keywords: Hypertension; blood pressure; blood pressure measurement; research standards; research; epidemiology.